PENINGKATAN PENGETAHUAN HAK KEKAYAAN INTELEKTUAL GURU-GURU MAN 3 JAKARTA DALAM MENUMBUHKAN KESADARAN BERKEKAYAAN INTELEKTUAL - Endang Purwaningsih; Chandra Yusuf; Mohammad Ryan Bakry (JURNAL PENGABDIAN AL-IKHLAS UNIVERSITAS ISLAM KALIMANTAN MUHAMMAD ARSYAD AL BANJARY, 2019)
In Article 14 of Law Number 14 of 2005 concerning Teachers and Lecturers, it is stated among other things the right of the teacher to obtain protection in carrying out duties and intellectual property rights; get the opportunity to improve competence; and obtain and utilize learning facilities and infrastructure to support the smooth functioning of professionalism; so it is appropriate if the teacher has intellectual property rights. Activities to increase teacher knowledge related to intellectual property rights have been well implemented, relevant to the interests of State Madrasah Aliyah 3 (MAN 3), and carried out by lecture and training methods with a participatory approach. There is a significant increase in MAN 3 teacher knowledge about the scope of IPR (20-60%). Likewise, IPR legal counseling can increase the knowledge of IPR teachers to be more aware of intellectual property by being done programmatically, synergies between community services Team, Structural MAN 3 and participants (teachers). Factors supporting the growth of teacher legal awareness of IPR include the development of the digital age of technology that must be well adapted by teachers in their profession and the need to protect teacher creativity and innovation. An obstacle to the growing legal awareness of teachers towards IPR is only to change the mindset that makes the module or work just meet the teacher's credit and the obligation of teaching materials for each teacher. Keywords: IPR, teacher, Madrasah Aliyah, Jakarta